2016
DOI: 10.1109/mitp.2016.52
|View full text |Cite
|
Sign up to set email alerts
|

M-Health Solutions Using 5G Networks and M2M Communications

Abstract: The authors present recent research linking the growing mobile health (m-health) field with the need for 5G and machine-to-machine technologies. They explore the multiple benefits that these emerging technologies could offer to broadly expand m-health solutions. Since the 1950s, the scientific and industrial communities have proposed using electronic and computer technology in healthcare. In recent decades, society has seen breakthroughs in technology that significantly change peoples' behavior and needs and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(33 citation statements)
references
References 8 publications
0
33
0
Order By: Relevance
“…They also stated that these technologies together can finally crack a dysfunctional healthcare system that has largely been impervious to technological innovations. Furthermore, the authors in [14] presented recent research linking the growing mobile health (mHealth) field with the need for 5G and machine-to-machine technologies. They explored the multiple benefits that these emerging technologies could offer to broadly expand mHealth solutions.…”
Section: Motivation and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…They also stated that these technologies together can finally crack a dysfunctional healthcare system that has largely been impervious to technological innovations. Furthermore, the authors in [14] presented recent research linking the growing mobile health (mHealth) field with the need for 5G and machine-to-machine technologies. They explored the multiple benefits that these emerging technologies could offer to broadly expand mHealth solutions.…”
Section: Motivation and Related Workmentioning
confidence: 99%
“…Additional research included in [16], where the authors introduced systems of wearable or implantable medical devices, and sensor systems for monitoring and transmitting physiological recorded signals, within a 5G infrastructure. Moreover, in [17] a potential 5G network and machine-tomachine communication was presented for developing and evolving mobile health applications. It is also worth mentioning that an initial research of this paper is also made in [18], where the authors proposed an IoT-Oriented architecture that enables the facilitation of concurrent IoT applications and services with diverse requirements based on dynamic 5G slices allocation.…”
Section: Motivation and Related Workmentioning
confidence: 99%
“…Telecom operators observe the technical challenges of IoT through systems, tools, devices, and platforms because their availability and integration complexity determines the opportunity to capture a share of the value that is generated by IoT implementation. Based on the literature review, it was found that the most commonly mentioned terms in this sense were related to: (1) ticketing system [201]; (2) monitoring: devices [199,[201][202][203][204]/services [199,201,202,205,206]/tools [207]/systems [11,12,199,201,205,206,[208][209][210]/ data [95,201]/framework [12,201]/solutions [20,205]/networks [211]/process [7]/activity [203,204,207]; (3) tracking technologies [4]/devices [204]/systems [204]/applications [11,210]/system [201]/services [202,205]; (4) [95,199]. This has led us to identify four activities, i.e., ticketing, monitoring, tracking, and managing/controlling, as new classification criteria of IoT applications.…”
Section: Activity-based Classification Of Iot Applicationsmentioning
confidence: 99%
“…In order to achieve network sustainability, required for 5G networks [216], spectrum efficiency needs to be improved 3-5 times [20,32,216]. Minimum peak spectrum efficiency is 30 bps/Hz for downlink and 15 bps/Hz for uplink [32].…”
Section: Spectrum Efficiencymentioning
confidence: 99%
“…We assume the spectrum handoff delay ‫,݈ݏ݇‬ is also added after the sensing slot in the CM2M gateways frames if the CM2M gateways decide to carry out channel switching after considering the sensing result and other thresholds. The CM2M gateways at the beginning of each transmission slot may choose to transmit data on the current channel, switch to another channel with a switch delay of ‫,݈ݏ݇‬ or stay on the current channel without transmitting; the primary transmission follows an on-off traffic model and is assumed to be continuous [8]. Fig.…”
Section: System Modelmentioning
confidence: 99%